Synthesis and characterization Of LiNi1_xZnxV04 4 - Rajammal, K.; Kufian, M.Z.; Majid, S.R.; Arof, Abdul Kariem (2009)
LiNil-xZnxV04 was synthesized at x = 0.0, 0.2, 0.4 and 0.8. by a polymer hybrid sol gel method. In this work acetates of lithium (C2H302Li), nickel (C2H302Ni) and zinc (C2H302Zn) with ammonium metavanadate (NH4V03) were used to synthesize t~e samples. These materials were dissolved in distilled water, stirred and heated continuously until a clear green solution was obtained. At this stage, a solution of chitosan in 1% acetic acid was added. The solution was continuously stirred and heated until it dried. The obtained precursor powder was sintered at 700°C for 3 hours. The crystallite size, lattice constant and surface morphology has been studied for zinc substituted LiNiV04. X-ray diffraction (XRD) exhibits peaks without impurities. Zinc substituted LiNiV04 shows decreasing crystallite size from x =' 0.0 to X = 0.4. Crystallite size increases again from x = 0.4 to x = 0.8. Cyclic voltammetric (CV) studies were performed.